2019
DOI: 10.1097/bsd.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Interbody Cage Subsidence Following Anterior Cervical Discectomy and Fusion

Abstract: Study Design: This is a prospective study. Objective: The purpose of this study was to analyze the factors influencing subsidence following anterior cervical discectomy and fusion (ACDF) using a stand-alone cage. Summary of Background Data: The relationship between cage subsidence and cage height and material has been reported in previous studies. Methods: Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…Increased compressive forces is another basic mechanism which drive to endplate fracture and CS [24]. DH over-distraction is widely accepted as risk factor for CS in reports covering cervical fusion surgery [25]. In our study, we found that the increase in DH distraction was signi cantly correlated with CS following OLIF.…”
Section: Discussionsupporting
confidence: 54%
“…Increased compressive forces is another basic mechanism which drive to endplate fracture and CS [24]. DH over-distraction is widely accepted as risk factor for CS in reports covering cervical fusion surgery [25]. In our study, we found that the increase in DH distraction was signi cantly correlated with CS following OLIF.…”
Section: Discussionsupporting
confidence: 54%
“…Early fusion can also reduce the frequency of follow-up imaging examinations and increase the confidence of spinal surgeons performing this surgical technique. At present, there are still a number of studies revealing that postoperative subsidence is related to poor clinical outcomes [28][29][30][31]. Igarashi et al [31] proposed that cage subsidence must be avoided in ACDF since it is often the cause of cervical foraminal stenosis and cage displacement.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are still a number of studies revealing that postoperative subsidence is related to poor clinical outcomes [28][29][30][31]. Igarashi et al [31] proposed that cage subsidence must be avoided in ACDF since it is often the cause of cervical foraminal stenosis and cage displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Cage subsidence is a common complication following ACDF and can result in the loss of disc height, disrupting the sagittal alignment of the spine, preventing solid fusion, and introducing restenosis of the foramina (9,10). However, the impacts of cage subsidence on clinical outcomes remain controversial for the cervical spine (11). Several factors have been proposed to contribute to cage subsidence, including aggressive endplate preparation, osteoporosis, differences in treatment levels, cage size, and cage material (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%